Reception of Slit requires only the chondroitin-sulphate-modified extracellular domain of Syndecan at the target cell surface. - Chanana, B.; Steigemann, P.; Jäckle, H.; Vorbrüggen, G. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
Syndecan (Sdc) is a conserved transmembrane heparan sulfate proteoglycan (HSPG) bearing additional chondroitin sulfate (CS) modifications on its extracellular domain. In vertebrates, this extracellular domain of Sdc is shed and acts as a soluble effector of cellular communication events, and its cytoplasmic domain participates in intracellular signaling needed to maintain epithelial integrity. In Drosophila, Sdc has been shown to be necessary for Slit signaling-dependent axon and myotube guidance during CNS development and muscle pattern formation. We report that Sdc acts in a cell-autonomous manner in Slit-receiving cells and that its membrane-anchored extracellular domain is sufficient to mediate Slit signaling. Sdc activity can be replaced by the human homolog hsdc2. However, the HSPG Dally-like protein (Dlp), which lacks CS modifications at its extracellular domain, can only partially substitute for Sdc function, and its activity is not restricted to the Slit target cells. Our results suggest that Sdc and Dlp act in a cooperative but nonredundant fashion in axon and myotube guidance. We propose that Dlp, which lacks CS modifications, participates in the transfer of Slit from its site of expression to the target cells, where CS-modified Sdc concentrates and presents the ligand.